A moderated mediation mechanism underlying the impact of website telepresence on purchase intention — Evidence from Chinese female college student customers - Zhu, Guiqin; Jiang, Shuaihe; Li, Kai (Frontiers in Psychology, 2022)
Telepresence in e-commerce, the feeling of resembling shopping in a physical store, plays a critical role in determining online purchase intention. However, the cognitive mechanism and boundary conditions about its effect still need further investigation. The current study construed flow experience and socioeconomic status as important variables and developed a moderated mediation model for their roles in the effect of telepresence. The model was supported by our study where a group of Chinese female college students participated in simulated online apparel shopping and completes relevant questionnaire surveys. The results show that: (1) website telepresence predicts positively the purchase intention of females, (2) flow experience mediates the impact of website telepresence on purchase intention, and (3) the relationship between website telepresence and flow experience could be moderated by socioeconomic status, namely, females with higher socioeconomic status demonstrate stronger mediation of flow experience. These findings can help researchers and online retailers understand the flow concept in e-commerce and formulate marketing strategies to retain consumers with different socioeconomic statuses.